ASSOCIATION OF CELIAC DISEASE IN PATIENTS WITH TYPE 1.5 DIABETES MELLITUS: A LITERATUR REVIEW - Setiawan MD, Daniel; Yumilia, Hoo (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Background: Celiac disease (CD) and type 1 diabetes are immune-mediated diseases that share common susceptibility factors, primarily HLA genetics. Objective and methods: This systematic review and meta-analysis sought data from Cochrane, PubMed, Googlescholar, and other journal databases. We searched for the keywords “celiac disease” and “diabetes melitus”. The inclusion criteria of the research to be included are research that examines the association of celiac disease in patients with type 1.5 diabetes melitus or latent autoimmune diabetes in adults (LADA), research subjects are adults (not animal), and use primary data. Result: All the studies found showed a close association between celiac disease and LADA or T1.5DM. Conclusion: LADA or type 1.5 DM and CD are autoimmune conditions that can coexist. HLA is a gene that plays a role in both diseases. Clear common risk factors, genetics and environment are likely to play an important role in the initiation of the condition.